2017
DOI: 10.1002/jts.22207
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Threat as a Mediator of Peritraumatic Stress Symptom Development During Wartime: An Experience Sampling Study

Abstract: Exposure and sense of threat have been associated with stress symptoms, yet these relationships have not been clarified during the peritraumatic period. We investigated the mediating role of sense of threat in the link between exposure to rocket warning sirens and stress symptoms during wartime, and the effect of severe mental illness (SMI) status and gender on this mediation. A 30-day twice-daily smartphone-based intensive assessment of exposure to sirens, sense of threat, and peritraumatic stress symptoms wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The present paper utilized data collected within a large prospective ESM study conducted during and after the Israel–Gaza conflict that took place in July and August 2014 (Gelkopf et al., ; Greene, ; Greene et al., ; Lapid Pickman, Greene, & Gelkopf, ). During the 50‐day conflict, rockets and mortar shells were fired at Israeli communities from Gaza, and the Israel Defence Forces conducted ground and air attacks on Gaza.…”
Section: Methodsmentioning
confidence: 99%
“…The present paper utilized data collected within a large prospective ESM study conducted during and after the Israel–Gaza conflict that took place in July and August 2014 (Gelkopf et al., ; Greene, ; Greene et al., ; Lapid Pickman, Greene, & Gelkopf, ). During the 50‐day conflict, rockets and mortar shells were fired at Israeli communities from Gaza, and the Israel Defence Forces conducted ground and air attacks on Gaza.…”
Section: Methodsmentioning
confidence: 99%
“…Analyses performed on the same data set as was used in the current study (Gelkopf et al., Greene et al., ; Lapid Pickman, Greene, & Gelkopf, ) have also suggested that the dynamics of P‐PTSS in civilian populations are affected by the level of objective threat (e.g., sounding of sirens at the time of incoming rocket fire). The aforementioned studies, as well as others, have also suggested gender (Freedman et al., ); a history of severe mental health problems, including poor emotional self‐regulation (Koenen, ), elevated perceived threat (Conway, Starr, Espejo, & Brennan, ), and weakened ability for contextual integration of information (Holmes & Steel, ); and trauma history (Goslin, Stover, Berkowitz, & Marans, ; Harvey & Bryant, ) as risk factors for acute stress reactions after a traumatic event.…”
mentioning
confidence: 71%
“…Arousal thus may only lead to other negative symptoms if it is experienced as a threat. Indeed, studies have suggested that threat is a better predictor of PTSD than exposure (Kolkow, Spira, Morse, & Grieger, ) itself or that threat mediates the connection between exposure and symptoms (Lapid Pickman et al., ). The negative cognitions and emotions along with the memories themselves might feed the arousal by triggering the fear circuitry or simply by boosting the arousal, or both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Threat perceptions have been found to be related both to war and terror (Bleich et al, 2003; Kutz & Dekel, 2006), as well as predicting posttraumatic psychopathology (Kolkow, Spira, Morse, & Grieger, 2007; Ozer et al, 2003; Razik, Ehring, & Emmelkamp, 2013; Vance et al, 2018). Furthermore, studies show that perceived threat plays a significant mediating role in the association between trauma exposure and both peri‐ and posttraumatic stress symptoms (Ehlers & Clark, 2000; Lapid Pickman et al, 2017). Understanding the role that peritraumatic reactions to trauma in general, and peritraumatic threat in particular, play in the development of posttraumatic psychopathology may have important implications for understanding and preventing the development of psychopathology following trauma exposure (Bovin & Marx, 2011; Ehlers & Clark, 2000).…”
Section: Introductionmentioning
confidence: 99%